SOX2 contributes to melanoma cell invasion - Girouard, Sasha D (2011)
The mechanisms of melanoma invasion are poorly understood despite extensive inquiry. SRY (sex determining region Y)-box 2 (SOX2) is an embryonic stem cell transcription factor that has recently been discovered to be expressed in human melanoma where it is associated with dermal invasion and primary tumor thickness. To assess the potential role of SOX2 expression in melanoma invasion, we examined patient melanomas and humanized melanoma xenografts, and noted preferential SOX2 expression in cells that interfaced and infiltrated dermal stroma. Experimental knockdown (KD) of SOX2 mRNA and protein in A2058 melanoma cells with high constitutive SOX2 expression resulted in 4.5-fold decreased invasiveness in vitro compared with controls (P<0.0001). Conversely, when G361 cells that normally express low SOX2 were transduced to overexpress SOX2 mRNA and protein, a 3.8-fold increase in invasiveness was observed (P=0.0004). Among 84 invasion-related genes, RT-PCR screening revealed that SOX2 KD resulted in striking decrease in matrix metalloproteinase-3 (MMP-3), an endopeptidase associated with cleavage of the extracellular matrix. Quantitatively, SOX2 KD diminished MMP-3 mRNA by 87.8%. MMP-3 KD in SOX2-expressing A2058 cells served to inhibit invasion, although to a lesser degree than SOX2 KD. Finally, immunostaining of patient and xenograft melanomas revealed coordinate SOX2 and MMP-3 expression in regions of stromal infiltration. These data implicate SOX2 expression in melanoma invasion, and suggest a role for MMP-3 as one potential mediator of this process.